Development of ethanol analysis in cough syrup medicine by colorimetric method - Sultan, Siti Fatimah; Susanti, Hari; Mohamed, Farahidah; Salamah, Nina; Farida, Verda (Journal of Halal Science and Research, 2025)
Cough syrup is a pharmaceutical preparation often containing ethanol as a solvent. However, the presence of ethanol in the drug can cause safety issues. This study aims to develop and validate a colorimetric method for determining ethanol in cough syrup. Cough syrup samples from different brands were analyzed using the method. The Visible spectrophotometric method uses the oxidation reaction of ethanol with potassium dichromate in an acidic condition. Method validation was conducted, including linearity, precision, accuracy, limit of detection (LOD), and limit of quantification (LOQ). The results showed this method had good linearity (r > 0.99) with a concentration range of 0.48 – 5.76 % (b/v). UV-Vis spectrophotometric method showed good precision and accuracy with SD = 0.0014, RSD = 0.4046 %, and % recovery = 99.99 %, while LOD = 0.1074 % and LOQ = 0.3253 %. This study concludes that the colorimetric method can be used as a valid and complementary method for analyzing ethanol content in cough syrup, providing important information for producers and consumers regarding product safety.   Keywords: Analytical method validation, Cough syrup, Ethanol, Spectrophotometry.